HR practices and employee performance: the mediating role of well-being. Issue 2 (12th February 2018) - Khoreva, Violetta; Wechtler, Heidi
Abstract : Purpose: The purpose of this paper is to examine the associations between the skill-, motivation- and opportunity-enhancing dimensions of human resource (HR) practices and in-role and innovative job performance. Furthermore, it considers the mediating effects of psychological, physical and social employee well-being on these associations. Design/methodology/approach: Structural equation modeling was utilized to analyze multi-source survey data from a sample of 300 employees and 34 immediate supervisors in a professional service company in Finland. Findings: The results indicate that whereas physical and social employee well-being partially mediate the association between skill- and opportunity-enhancing HR practices and in-role job performance, psychological employee well-being partially mediates the association between motivation-enhancing HR practices and innovative job performance. Research limitations/implications: Given its cross-sectional nature, the authors cannot completely exclude the possibility of common method bias influencing the study results. The authors thus call for longitudinal research to examine the nature of causality within the associations analyzed in the study. Originality/value: This study does not support the notion of trade-offs between HR practices, employee well-being and employee performance. Instead, it illustrates that even though different dimensions of HR practices enhance different dimensions of employee well-being, which, in turn, increase different types of employee performance, the different dimensions of HR practices work in the same direction and do not generate any unintended consequences in terms of reduced employee physical well-being.